Analysis of Evaluation of Islamic Religious Education Learning Class V at SDN 158 Palembang - Mardiah Astuti; Mutyati Mutyati; Wulan Okta Bela; Elisa Arni Anggraini; Fifi Nur Hidayanti (Sustainable, 2024)
This study aims to analyze the evaluation of Islamic Religious Education (PAI) learning in grade V of SDN 158 Palembang, focusing on the implementation, effectiveness, and challenges faced. The research uses a descriptive qualitative method, collecting data through in-depth interviews, observations, and document studies. The study subjects include PAI teachers and grade V students as the primary data sources. The study results show that learning evaluation is carried out in an integrated manner covering cognitive, affective, and psychomotor aspects. Teachers use written tests to measure conceptual understanding, attitude observation to assess students' character, and hands-on practice to evaluate worship skills. This evaluation has provided a comprehensive picture of student achievement, although obstacles such as limited time for in-depth assessment and lack of standardized evaluation tools have been found. Observations revealed that the direct practice-based approach was more effective in building students' understanding of the teaching material than conventional evaluation methods. This study concludes that although the evaluation of PAI learning has been reasonably practical, developing a more structured and technology-based evaluation system is still needed to improve the efficiency and accuracy of assessment. The implications of this study emphasize the importance of individualized guidance for students and strengthening teacher competence in carrying out holistic-based learning evaluations. These findings can be the basis for developing PAI education policies at the elementary school